2019
DOI: 10.4103/aer.aer_81_19
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided erector spinae versus ilioinguinal/iliohypogastric block for postoperative analgesia in children undergoing inguinal surgeries

Abstract: Context: Erector spinae plane (ESP) block is a promising technique in the field of pediatric postoperative analgesia considering its safety and simplicity. Objective: The objective of the study is to compare the efficacy of ultrasound (US)-guided ilioinguinal/iliohypogastric nerve (IIN) block and ESP block for postoperative analgesia after pediatric unilateral inguinal hernia repair. Patients and Methods: Sixty patients randomized into two eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 20 publications
0
6
0
2
Order By: Relevance
“…Previous studies have shown the efficacy of ESPB after OIHR surgery in both adult and pediatric patients [ 27 , 28 ]. El-Emam and El Motlb [ 27 ] administered ESPB to children at a volume of 0.5 ml/kg from the L1 transverse process and found a lower rescue analgesic requirement, lower FLACC scores, and a longer time to first analgesic request compared to the II-IH block in OIHR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown the efficacy of ESPB after OIHR surgery in both adult and pediatric patients [ 27 , 28 ]. El-Emam and El Motlb [ 27 ] administered ESPB to children at a volume of 0.5 ml/kg from the L1 transverse process and found a lower rescue analgesic requirement, lower FLACC scores, and a longer time to first analgesic request compared to the II-IH block in OIHR.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown the efficacy of ESPB after OIHR surgery in both adult and pediatric patients [ 27 , 28 ]. El-Emam and El Motlb [ 27 ] administered ESPB to children at a volume of 0.5 ml/kg from the L1 transverse process and found a lower rescue analgesic requirement, lower FLACC scores, and a longer time to first analgesic request compared to the II-IH block in OIHR. Sakae et al [ 28 ] performed ESPB at T8 level with 20 ml ropivacaine (0.5%) LA, determined that it did not reduce the rescue analgesic requirement, and reported that it was ineffective for OIHR.…”
Section: Discussionmentioning
confidence: 99%
“…However, with the technological progress and the emergence of various new trunk block techniques, II/IHNB has entered a controversial era. Some kinds of literature have confirmed that ESPB is superior to II/ IHNB in inguinal surgery analgesia (El-Emam, et al, 2019). Nevertheless, compared with TAPB, II/IHNB alsohas some advantages in inguinal analgesia (Faiz, et al, 2019).…”
Section: Ilioinguinal/iliohypogastric Nerve Block (Ii/ihnb)mentioning
confidence: 99%
“…-bloqueo del erector espinal: Descrito en 2016 por Forero, ha ganado amplia popularidad desde entonces. Al compararlo con el bloqueo IL/IH en cirugías inguinales, mejoró el manejo del dolor disminuyendo la necesidad de analgesia de rescate, y aumentó el tiempo de duración de la analgesia y la satisfacción parental, sin diferencias en efectos adversos [23]. Si bien faltan estudios randomizados que lo avalen y el mecanismo de acción no está del todo claro, constituye una buena alternativa analgésica en este tipo de cirugías, por su posible efecto en dolor visceral junto con proveer analgesia de pared abdominal [23].…”
Section: Dolor Posoperatorio En Cirugía Ambulatoria Pediátricaunclassified
“…Al compararlo con el bloqueo IL/IH en cirugías inguinales, mejoró el manejo del dolor disminuyendo la necesidad de analgesia de rescate, y aumentó el tiempo de duración de la analgesia y la satisfacción parental, sin diferencias en efectos adversos [23]. Si bien faltan estudios randomizados que lo avalen y el mecanismo de acción no está del todo claro, constituye una buena alternativa analgésica en este tipo de cirugías, por su posible efecto en dolor visceral junto con proveer analgesia de pared abdominal [23]. -bloqueo de nervio pudendo: En estudios observacionales de niños sometidos a circuncisión, reparación de hipospadia y otras cirugías peneanas, demostró no inferioridad comparado con BC en cuanto a analgesia posoperatoria.…”
Section: Dolor Posoperatorio En Cirugía Ambulatoria Pediátricaunclassified